Analisis Pola Konsumsi dan Tingkat Kerawanan Pangan Petani Lahan Kering di Kabupaten Gunungkidul (Studi Kasus di Desa Giritirto, Kecamatan Purwosari, Gunungkidul) - Widodo, Aris Slamet; Wulandari, Retno (AGRARIS: Journal of Agribusiness and Rural Development Research, 2016)
Gunungkidul was being as an extreme nature and categorized as marginal land which was cause food shortages in some districts. One of the district experienced food shortages in 2013 was Purwosari.Â  This research aimed to find out the food consumption patterns and relation among land area, income and educational levels of the dry land farmers toward the food shortages level. The research method used in this study was descriptive technique by giving explanation from statistic data (percentage, mean, data range, frequency distribution, cross tabulation). Moreover, in order to measure the food shortages leve this study used the comparison formula between the number of poor people consuming food with the nutrition daily value as much as 2,150 calories. The research findings show that the average daily individual consumption was 1274.25 Kkal, and categorized as people who are extremely food shortages. The calories are mostly gained from consuming rice, corn and tempe, as daily consumption patterns. The levels of farmersâ income, farming land areas, and level of education are not related to the food shortages level.